Advancing intercalation strategies in layered hybrid perovskites by bringing together synthesis and simulations - Lin-Jie Yang; Wenye Xuan; Sara Henda; Shaoyang Wang; Sai Kiran Rajendran; David B. Cordes; David N. Miller; Alexandra M. Z. Slawin; Lethy Krishnan Jagadamma; Hamid Ohadi; Hsin-Yi Tiffany Chen; Matthew S. Dyer; et al. (Nature Communications)
Abstract Finding ways to modify the electronic structure of halide perovskites is desireable as they have applications in a variety of devices, from photovoltaics to LEDs. Additionally, designing functional materials can be facilitated through the use of computation. Here, we have used a combination of synthesis and computation to screen for intercalated, layered hybrid perovskites. 54 compositions were screened and five compounds containing intercalated halogens were prepared as single crystals. A further compound, which was not screened and contained IBr, was prepared. We computationally identified an intercalated layered hybrid perovskite with a low bandgap and prepared it as a thin-film. Through examination of single crystal X-ray diffraction data, we provide some design guidelines for intercalation. The conformational flexibility in the organic ammonium cation allows rotations in the carbon backbone which change upon intercalation. Optoelectronic properties were studied using photoluminescence spectroscopy and preliminary photovoltaic device testing.